Antimicrobial photodynamic therapy adjuvant to non-surgical periodontal therapy in patients with diabetes mellitus: A meta-analysis - Abduljabbar, Tariq; Vohra, Fahim; Javed, Fawad; Akram, Zohaib (Photodiagnosis and photodynamic therapy, 2017)
To determine whether treatment with antimicrobial photodynamic therapy (aPDT) as an adjunct to scaling and root planing (SRP) improves periodontal clinical and glycemic outcomes in chronic periodontitis patients (CP) with type 2 diabetes mellitus (DM). Databases (MEDLINE via PubMed; EMBASE; Cochrane Central Register of Controlled Trials and Cochrane Oral Health Group Trials Register databases) were searched up to and including October 2016. The addressed PICO question was: “What are the effects of aPDT as an adjunct to SRP in terms of periodontal and glycemic outcomes as compared to SRP alone in individuals with DM?” Four randomized clinical trials were included in the present review. All studies reporting clinical periodontal and metabolic parameters, showed that aPDT was effective in the treatment of CP in DM subjects at follow up. Considering the effects of aPDT as an adjunct as compared to SRP alone on clinical signs of CP in DM subjects, no difference could be observed for all evaluated parameters (PD: Z=−0.61, P=0.54; CAL: Z=0.27, P=0.78; HbA1c: Z=0.138, P=0.89) It remains debatable whether aPDT is effective as an adjunct to SRP than SRP alone in patients having CP with DM, given that the scientific evidence is weak. In terms of periodontal parameters and glycemic levels, aPDT does not provide additional benefit in the treatment of CP in DM patients. However, further randomized clinical trials with standard laser parameters and long follow up periods are warranted to study periodontal and glycemic outcomes in this regard.